Intracranial injection of natural killer cells engineered with a HER2-targeted chimeric antigen receptor in patients with recurrent glioblastoma - Burger, Michael C; Forster, Marie-Therese; Romanski, Annette; Straßheimer, Florian; Macas, Jadranka; Zeiner, Pia S; Steidl, Eike; Herkt, Stefanie; Weber, Katharina J; Schupp, Jonathan; Lun, Jennifer H; Strecker, Maja I; et al. (Neuro-oncology (Charlottesville, Va.), 2023)
Abstract Background Glioblastoma (GB) is incurable at present without established treatment options for recurrent disease. In this phase I first-in-human clinical trial we investigated safety and feasibility of adoptive transfer of clonal chimeric antigen receptor (CAR)-NK cells (NK-92/5.28.z) targeting HER2, which is expressed at elevated levels by a subset of glioblastomas. Methods Nine patients with recurrent HER2-positive GB were treated with single doses of 1 × 107, 3 × 107, or 1 × 108 irradiated CAR-NK cells injected into the margins of the surgical cavity during relapse surgery. Imaging at baseline and follow-up, peripheral blood lymphocyte phenotyping and analyses of the immune architecture by multiplex immunohistochemistry and spatial digital profiling were performed. Results There were no dose-limiting toxicities, and none of the patients developed a cytokine release syndrome or immune effector cell-associated neurotoxicity syndrome. Five patients showed stable disease after relapse surgery and CAR-NK injection that lasted 7 to 37 weeks. Four patients had progressive disease. Pseudoprogression was found at injection sites in 2 patients, suggestive of a treatment-induced immune response. For all patients, median progression-free survival was 7 weeks, and median overall survival was 31 weeks. Furthermore, the level of CD8+ T-cell infiltration in recurrent tumor tissue prior to CAR-NK cell injection positively correlated with time to progression. Conclusions Intracranial injection of HER2-targeted CAR-NK cells is feasible and safe in patients with recurrent GB. 1 × 108 NK-92/5.28.z cells was determined as the maximum feasible dose for a subsequent expansion cohort with repetitive local injections of CAR-NK cells.